EFFECT OF NIGELLA SATIVA SEED EXTRACT ON THE VIABILITY OF CANDIDA GLABRATA - DIBA, FARAH; FARIDA, RATNA; REDJEKI, SRI (International Journal of Applied Pharmaceutics, 2019)
Objective: Candidiasis is a common opportunistic infection of the oral cavity caused by a yeast-like fungus called Candida. Candida glabrata is the second most frequently isolated species from this condition, after Candida albicans. This study aimed to evaluate the effect of Nigella sativa (black cumin), known to possess antifungal properties, on the viability of C. glabrata. Methods: C. glabrata was added to a 96-microwell plate that was coated with artificial saliva and exposed to various concentrations (6.25%, 12.5%, 25%, and 50%) of N. sativa seed extract; amphotericin B (250 mg/mL) was used as the positive control and 200 μL of yeast nitrogen base medium as the negative control. The viability percentage of C. glabrata was determined by MTT assay. Results: The results showed that the viability values of C. glabrata were lower after exposure to the N. sativa seed extract when compared with the negative control. Conclusion: The viability of Candida glabrata was decreased with increasing concentrations of the extract.